Aerospace series. Electrical cables, installation. Protection sleeve in meta-aramid fibres. Self-wrapping fire protection sleeve, flexible, post installation, operating temperature from -55 °C to 260 °C. Product standard Part 009, (30th April 2016) - British Standards Institution,
No abstract available